STRATEGI PENGEMBANGAN PRODUK UMKM RAMEN DI KOTA BATAM: PENDEKATAN HOUSE OF QUALITY UNTUK KEUNGGULAN KOMPETITIF - Putri, Angela; Lawi, Ansarullah; Bora, M. Ansyar (Universitas Putera Batam, 2024)
This study aims to analyze and prioritize customer needs using the House of Quality (HoQ) approach in ramen UMKM in Batam City, and to link customer needs with relevant technical features. Data were collected through a survey of 38 consumers of “Uru Ramen” UMKM in Batam, followed by analysis of the validity and reliability of the survey instrument using statistical methods. The results showed that all survey items were valid and reliable. The HoQ analysis revealed that the quality of raw materials and cleanliness were the top priorities for customers. The selection and supervision of suppliers and routine cleaning schedules were the most influential technical factors in meeting these needs. This study also showed that “Uru Ramen” UMKM had strengths in taste quality with an average user value of 41,289, but weaknesses in price portion and ease of access. Recommendations were given to improve aspects that were less competitive and maintain the quality of raw materials and cleanliness in order to increase customer satisfaction and the competitiveness of ramen UMKM in Batam City.